A Perspective on Veterinary Forensic Pathology and Medicine in the United Kingdom. (September 2016) - Newbery, S. G.; Cooke, S. W.; Martineau, H. M.
Internationally, forensic medicine and pathology are increasingly recognized as an important aspect of work done by veterinary clinicians and veterinary pathologists. In this article, a forensic veterinary clinician, a forensic veterinary pathologist in private practice, and a forensic veterinary pathologist at a veterinary school discuss the interactions among veterinary clinicians, veterinary pathologists, and law enforcement agencies and how future interactions can be improved. The focus is on the United Kingdom, but many of the principles, challenges, and suggestions are applicable to other jurisdictions. Clinicians and pathologists require forensic training to enable them to apply their veterinary knowledge to suspected cases of animal abuse and to subsequently present their findings and conclusions to a court of law in a concise, professional, and unbiased manner, and some opportunities for such advanced training in the United Kingdom are indicated. It is important that forensic veterinary clinicians and pathologists interact in an unbiased and collegial manner to answer the questions posed by courts of law. Opportunities for improved training, communication, and interaction among forensic veterinarians, forensic scientists, and law enforcement are discussed.